Polish Community of the ’Internal Borderlands’ at the Turn of the 20th and 21st Centuries. Cultural and Identity Changes - Kurek , Halina (Papers in Linguistics, 2023)
The objective of the article is to present the changes that, after 1989, and particularly after 2004, occurred in the language and culture of the Polish communities living in the internal (territorial, virtual and individual) borderlands and their influence on the cultural identity of Poles. These changes are discussed based on materials collected in southern Poland (in the regins of Nowy Sącz and Podhale) and in the Low Beskid mountains in south-eastern Poland. By ‘internal (psychological, individual) borderland’ within a country, the author refers to the contact between two linguistic and cultural complexes: the rural and the municipal one, as well as the virtual borderland of two cultures: the national and the regional, i.e. local culture (related to one’s identity), and techno-managerial culture, which has a global range.